Acoustic Metasurfaces: Hollow‐Out Patterning Ultrathin Acoustic Metasurfaces for Multifunctionalities Using Soft fiber/Rigid Bead Networks (Adv. Funct. Mater. 36/2018). (3rd September 2018) - Tang, Hanchuan; Chen, Zhesi; Tang, Ni; Li, Shuaifeng; Shen, Yaxi; Peng, Yugui; Zhu, Xuefeng; Zang, Jianfeng
Abstract : In article number1801127, Xuefeng Zhu, Jianfeng Zang, and co‐workers describe an ultrathin metasurface (a 650 th of the wavelength) that imparts soundwaves with a non‐trivial phase shift and more than 80% transmittance. The thinness of the surface makes It accessible to processing similar to paper‐cutting‐art, thereby introducing a variety of functions, including acoustic vortexes, focusing, and super‐resolution.